Análisis comunicacional de las relaciones públicas del GAD Quevedo, y su incidencia habitantes de la Parroquia San Cristóbal Sector Cooperativa Abdón Calderón del cantón Quevedo en al año 2021 - Vanoni Reyes, Erika Mariana (2021)
Politics and democracy constitute great elements of today's society, for them it is essential that there is a good harmony that generates peace and security, considering these factors it is necessary to investigate the public relations that the inhabitants of the San Cristóbal parish have in the sector of the Abdón Calderón cooperatives of the Quevedo canton, with the authorities of the cantonal Gad, The municipal Gad of the Quevedo canton is a public administrative entity that plans, controls and executes for the welfare of the citizens, as a non-profit administrative entity must have a corporate communication plan because through that information is transmitted to internal staff and external citizens and in this way to establish an empathy between both, said communication must be dynamic, planned and concrete. It is necessary for the researcher to deepen and apply their knowledge allowing to establish methods and strategies with the aim of having excellent internal and external communication, counting on the weakness of the municipal Gad that empirically applies the media in this way. Citizens will benefit by improving their public relations with the municipal Gad since the two need each other for the development of social progress.